Decentralization and Citizen Perception of Prosperity in Indonesia - Nanda Wijayanti; Matthew Mingus (AKRUAL: JURNAL AKUNTANSI, 2022)
This article contributes to research on the impact of decentralisation reforms on local and regional prosperity. Researchers argue that implementing decentralization reforms can encourage citizens to participate in policy making. To test the idea, this study examines the relationship between fiscal decentralisation, administrative autonomy, direct local elections, and citizen prosperity using the Indonesia Family Live Survey (IFLS) 2007. IFLS is a longitudinal survey that uses face-to-face interviews with adult Indonesians (N individuals = 29,000, N districts = 262). Using ordered logistic regression, we find that fiscal and administrative decentralisation increases the probability that citizens feel prosperous, while direct local elections do not appear to have this effect. This relationship is stronger when the decentralisation reform is conducted in a less-corrupt institutional environment. The findings suggest that decentralisation in the weak political system may improve local prosperity through the improved capacity of Indonesian districts to deliver public services rather than through the opportunities for citizens to participate in local elections